The Effectiveness of the Use of Digital Technologies in Management Activities - Jo’rayev Vohid Tojimamatovich (Global Scientific Publishing, 2022)
The use of digital technologies leads to the achievement of qualitatively new educational results, accelerates the process of management activities and, in general, increases its efficiency. The use of digital technologies in the management of education will increase the quality and culture of management activities by an order of magnitude, and create reserves for working in the development mode.
Keywords: digital technologies; management of an educational organization; reserves